Kaitan Gender dan Struktur Keluarga dengan Pemberian Intervensi Gizi Spesifik pada Anak Usia 6-23 Bulan - Hutagaol, Rutmauli; Pratiwi, Niken; Fratama, Ferry Fadli; Fauziah, Erna (Journal of Telenursing (JOTING), 2024)
This study aimed to explore the relationship between gender and family structure by providing specific nutritional interventions to children aged 6-23 months. The method used was analytical observational with a cross-sectional approach. The research results from chi-square analysis showed that there was a significant relationship between the child's gender and family type and the provision of specific nutrition (p value <0.05). The majority of male children received positive specific nutrition, namely 52.2%, and girls received positive specific nutrition, namely 64.9%. The nuclear family type provided specific nutrition positively by 63.1% and the large family type provided specific nutrition negatively by 52.8%. In conclusion, the child's gender and family type have a significant influence on the provision of specific nutrition and nuclear families are more likely to provide better nutrition. Keyword: Child's Gender, Provision of Specific Nutrition, Stunting, Family Type